Clinical and Molecular Properties of Human Immunodeficiency Virus-Related Diffuse Large B-Cell Lymphoma - de Carvalho, Pedro S.; Leal, Fabio E.; Soares, Marcelo A. (Frontiers in Oncology, 2021)
Non-Hodgkin lymphoma is the most common malignancy affecting people living with HIV (PLWH). Among its several subtypes, diffuse large B-cell lymphoma (DLBCL) is an important manifestation within the HIV-infected compartment of the population. Since HIV is able to modulate B cells and promote lymphomagenesis through direct and indirect mechanisms, HIV-related DLBCL has specific characteristics. In this review, we address the clinical and molecular properties of DLBCL disease in the context of HIV infection, as well as the mechanisms by which HIV is able to modulate B lymphocytes and induce their transformation into lymphoma.